Aplikasi Konversi Aksara Sunda Ke Bahasa Indonesia Berbasis Web Menggunakan PHP Mysql - Abdul Haris; Nina Nirmaya (KILAT, 2015)
Internet is an information technology that is rapidly growing these days. Technological developments and the needs of information led to increased complexity of information that should be processed, so that the need for information such as a website together increasingly necessary, a tool for delivering information and media to learn quickly and easily.Internet is also a means to study our own culture. For example, to learn about language and Sundanese script. Public or the user wants the ease of learning the language according to their pronunciation is difficult to pronounce. Also of course want to know the meaning of the word itself. In order for someone other than that derived from the Sundanese region can learn it easily, then made application to the conversion of Indonesian Sundanese script using PHP and MySQL.In designing the system using PHP and MySQL as database design media, Adobe Dreamweaver CS3 as a media interface design. In this application the user is given the ease of pronunciation of words contained in the language that is spoken by the sometimes difficult for people outside the Sundanese and displayed in Sundanese script translation.